Frailty in cerebellar ischemic stroke—The significance of temporal muscle thickness - Dubinski, Daniel; Won, Sae-Yeon; Mattes, Isabell; Trnovec, Svorad; Behmanesh, Bedjan; Cantré, Daniel; Baumgarten, Peter; Dinc, Nazife; Konczalla, Juergen; Wittstock, Matthias; Freiman, Thomas M.; Gessler, Florian (Frontiers in Neurology, 2023)
While comprising only 2% of all ischemic strokes, cerebellar strokes are responsible for substantial morbidity and mortality due to their subtle initial presentation and the morbidity of posterior fossa swelling. Further, low temporal muscle thickness (TMT) has recently been identified as a prognostic imaging parameter to assess patient frailty and outcome. We analysed radiological and clinical data sets of 282 patients with cerebellar ischemic stroke. Our analysis showed a significant association between low TMT, reduced NIHSS and mRS at discharge (p=0.035, p=0.004) and reduced mRS at 12-month (p=0.001). TMT may be used as a prognostic imaging marker and objective tool to assess outcome in patients with cerebellar ischemic stroke.